Hospital Architecture Adaptability: A Systematic Analysis of Concepts, Implementation, and Measuring Tools - Pandu Dewanata; Revianto Budi Santosa; Yulianto Purwono Prihatmaji (Jurnal Indonesia Sosial Teknologi, 2025)
This research aims to explore the concept of adaptability in hospital architecture through a systematic literature review. The methodology used was Systematic Literature Review (SLR) with PRISMA approach, utilising Watase Uake platform for analysis for the analysis of 26 selected articles published between 2015 and 2024. The results show that the need for adaptability of hospital architecture is driven by advances in medical technology, demographic changes, and learning from the COVID-19 pandemic. Findings reveal that the implementation of modular design, separation of building systems into independent layers, and integration of information technology can facilitate building adaptability. The development of measurement tools from simple qualitative approaches to comprehensive models such as GAAT, OBAT, and OFAT designed specifically for healthcare facilities. However, their implementation still faces gaps especially in different local contexts. This research contributes to the understanding of the importance of adaptability in hospital design and highlights the need for the development of more specific measurement tools for the Indonesian context.